Integrative description of two new species of the Xenylla maritima species complex (Collembola: Hypogastruridae) from Crete (Greece), with notes on the high intraspecific genetic divergence found in X. maritima Tullberg, 1869 - Dariusz Skarżyński; Barbara Valle; Dariusz J. Gwiazdowicz; David Porco (European Journal of Taxonomy)
A classical taxonomic analysis of materials from several European museums as well as our own collection along with the analysis of DNA barcoding data (cox1) allowed us to determine the taxonomic status of Cretan forms included in the recently revised Xenylla maritima complex. Two of them are recognized as distinct species: Xenylla ellisi sp. nov. and Xenylla schulzi sp. nov., and a new cryptic lineage was found within the morphological boundaries of the broadly distributed species X. maritima.